(untitled) - Siegel, Joel G. (Hauppauge, N.Y., 1994)
This reference explains 2,500 terms used in financial accounting, managerial and cost accounting, auditing, financial statement analysis, tax preparation, and economics. Appropriate for college students and business professionals, the topics include capitalization, deferred charge, gross domestic product, hedge fund, market value method, stock option, and value added tax.
Keywords: Accounting,Accounting; Terminology